Reggae Arrangement and Structure of Uncle Djink's "Kemesraan" - Arosicha Margusviana, Dea (Repertoar, 2025)
Music has been a part of life all along. In people's lives, music becomes a means of entertainment and a form of self-expression. In its development, each piece of music has characteristics and several types or genres that fit the tastes of all people.This research aims to analyze the song form and arrangement structure of the reggae version of Kemesraan by Uncle Djink. This research was conducted through a qualitative approach. The object studied is the form and arrangement of the Reggae Version of Kemesraan by Uncle Djink. The results of this research can be concluded as follows: The song form of Kemesraan by Reggae Uncle Djink uses the Big Band format in its arrangement. The instrument format is found in the writing of the song Kemesraan by Reggae Uncle Djink in full score. The arrangement structure of the Reggae version of the song "Kemesraan" by Uncle Djink has 110 beats and uses the basic scale A. In addition, the tempo chosen is 85 bpm, or, from the classical point of view, it is called Andante. The format used in the song "Kemesraan" Uncle Djink The genre applied to the song "Kemesraan" Uncle Djink is the Pop Reggae genre.